Genetic approaches for assessment of phosphorus use efficiency in groundnut (Arachis hypogaea L.) - Sai Rekha Kadirimangalam; Yashoda Jadhav; K. V. Nagamadhuri; Latha Putta; Tharanya Murugesan; Murali T. Variath; Anil Kumar Vemula; Surendra Singh Manohar; Sunil Chaudhari; Sunita Choudhary; Jana Kholova; Janila Pasupuleti (Scientific Reports, 2022)
Abstract Production of phosphorus efficient genotypes in groundnut can improve and also reduces environmental pollution. Identification of P-efficient groundnut genotypes is a need of the hour to sustain in P-deficient soils. The pot experiment showed significant differences between genotypes (G) and treatments (T) for all the traits and G × T interaction for majority of traits. The G × T × Y interaction effects were also significant for all the traits except leaf P% (LP%), leaf acid phosphatase (LAP) and root dry weight (RDW). In lysimeter experiment, the effect of G, T and G × T were significant for leaf dry weight (LDW), stem dry weight (SDW), total transpiration (TT) and transpiration efficiency (TE). For traits, LDW, SDW, TT, TE, ICGV 00351 and ICGS 76; for SDW, TT, ICGV 02266 are best performers under both P-sufficient and deficient conditions. Based on P-efficiency indices and surrogate traits of P-uptake, ICGV’s 02266, 05155, 00308, 06040 and 06146 were considered as efficient P-responding genotypes. From GGE biplot, ICGV 06146 under P-deficient and TAG 24 under both P-sufficient and deficient conditions are portrayed as best performer. ICGV 06146 was identified as stable pod yielder and a promising genotype for P-deficient soils. The genotypes identified in this study can be used as a parent in developing mapping population to decipher the genetics and to devleop groundnut breeding lines suitable to P-deficient soils.